Novel selection paradigms for endovascular stroke treatment in the extended time window. Issue 11 (11th June 2021) - Bouslama, Mehdi; Haussen, Diogo C; Rodrigues, Gabriel; Barreira, Clara; Frankel, Michael; Nogueira, Raul G
Abstract : Background and purpose: The optimal selection methodology for stroke thrombectomy beyond 6 hours remains to be established. Methods: Review of a prospectively collected database of thrombectomy patients with anterior circulation strokes, adequate CT perfusion (CTP) maps, National Institute of Health Stroke Scale (NIHSS)≥10 and presenting beyond 6 hours from January 2014 to October 2018. Patients were categorised according to five selection paradigms: DAWN clinical-core mismatch (DAWN-CCM): between age-adjusted NIHSS and CTP core, DEFUSE 3 perfusion imaging mismatch (DEFUSE-3-PIM): between CTP-derived perfusion defect (Tmax >6 s lesion) and ischaemic core volumes and three non-contrast CT Alberta Stroke Program Early CT Score (ASPECTS)-based criteria: age-adjusted clinical-ASPECTS mismatch (aCAM): between age-adjusted NIHSS and ASPECTS, eloquence-adjusted clinical ASPECTS mismatch (eCAM): ASPECTS 6–10 and non-involvement of the right M6 and left M4 areas and standard clinical ASPECTS mismatch (sCAM): ASPECTS 6–10. Results: 310 patients underwent analysis. DEFUSE-3-PIM had the highest proportion of qualifying patients followed by sCAM, eCAM, aCAM and DAWN-CCM (93.5%, 92.6%, 90.6%, 90% and 84.5%, respectively). Patients meeting aCAM, eCAM, sCAM and DAWN-CCM criteria had higher rates of 90-day good outcome compared with their non-qualifying counterparts(43.2% vs 12%, p=0.002; 42.4% vs 17.4%, p=0.02; 42.4% vs 11.2%, p=0.009; and 43.7% vs 20.5%, p=0.007, respectively). There was no difference between patients meeting DEFUSE-3-PIM criteria versus not(40.8% vs 31.3%, p=0.45). In multivariate analysis, all selection modalities except for DEFUSE-3-PIM were independently associated with 90-day good outcome. Conclusions: ASPECTS-based selection paradigms for late presenting and wake-up strokes ET have comparable proportions of qualifying patients and similar 90-day functional outcomes as DAWN-CCM and DEFUSE-3-PIM. They also might lead to better outcome discrimination. These could represent a potential alternative for centres where access to advanced imaging is limited.